Comparative and reliability studies of neuromechanical leg muscle performances of volleyball athletes in different divisions - Un, C. -P.; Lin, K. -H.; Shiang, T. Y.; Chang, E. -C.; Su, S. -C.; Wang, H. -K. (European Journal of Applied Physiology, 2013)
This study compared neural profiles of the leg muscles of volleyball athletes playing in different divisions of Taiwan`s national league to analyse the reliability and correlations between their profiles and biomechanical performances. Twenty-nine athletes including 12 and 17 from the first and second divisions of the league, respectively, were recruited. The outcome measures were compared between the divisions, including soleus H-reflex, first volitional (V) wave, normalised rate of electromyography (EMG) rise (RER) in the triceps surae muscles, and RER ratio for the tibialis anterior and soleus muscles, normalised root mean square (RMS) EMG in the triceps surae muscles, antagonist co-activation of the tibialis anterior muscle, rate of force development (RFD), and maximal plantar flexion torque and jump height. Compared to the results of the second division, the neural profiles of the first division showed greater normalised V waves, normalised RER in the lateral gastrocnemius, and normalised RMS EMG of the soleus and lateral gastrocnemius muscles with less antagonist co-activation of the tibialis anterior. First division volleyball athletes showed greater maximal torque, jump height, absolute RFD at 0-30, 0-100, and 0-200 ms, and less in the normalised RFD at 0-200 ms of plantar flexion when compared to the results of those in the second division. Neural profiles correlated to fast or maximal muscle strength or jump height. There are differences in the descending neural drive and activation strategies in leg muscles during contractions between volleyball athletes competing at different levels. These measures are reliable and correlate to biomechanical performances.